The mistletoe secret - Evans, Richard Paul (New York : Simon & Schuster, 2016)
Thinking no one is reading, a blogger who calls herself LBH writes about her most personal feelings, especially her overwhelming loneliness. She goes from day to day showing a brave face to the world while inside she longs to know how it would feel if one person cared about her. Alex Bartlett cares. He's reading her posts in Daytona Beach, Florida. Nursing his own broken heart and trust issues, he finds himself falling for this sensitive, vulnerable woman whose feelings mirror his own.
Keywords: Families -- Fiction; Holidays -- Fiction; Christmas stories; Romance fiction; Love stories